Habitat Characteristics and Density of Crab (Parathelphusa pardus) in Swamp Waters, Sawah Village, North Kampar District, Riau Province - Ramona, Witri; Fajri, Nur El; Fauzi, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
AbstractFreshwater crab is widely distributed in river, lake, swamp, canal, and pond. Riau Province has many freshwater crabs, however habitat characteristics information of these organisms are poorly known. This study in Sawah village from the Kampar Utara District, Province of Riau aimed to understand the habitat caracteristics of freshwater crab types in had been collected on june 2021 with random collection method using a bamboo traps and scoop net with 3 sampling sites in the Sawah village . There were trapped 27 crabs and all of them belonged to a single, Gecarcinucidae Family, Parathelpusa Genus. The crab most have been foundon first sampling site and avarage density is 1,42 ind/m2 were obtained from the shallow riverines with aquatic vegetation are most numerous from second and third sampling sites other. The value of water qualityparameters measured were temperature 30oC, transperancy  and depth 34-55 cm, pH 5, dissolved oxygen 7,2-8,0 mg/L and free carbondioxide 0,4-0,5 mg/L. Based on the results of PPNo. 22 Year of 2021 Class number II aboutwater quality management and water pollution controlit can be concluded that the habitat of Parathelpusa in Riau is shallow riverine with dense aquatic vegetation.Keywords: Freshwater crab, Gecarcinucidae, Parathelphusa, Kampar